Development of residential flood depth-damage curve for Kuantan, Pahang - Muhammad Aiman, Mat Jamil (2019)
Rapid development and inefficient flood management is the main factor for the occurring of flood event. A precise estimation of flood damage is needed to ensure a compressive management of flood risk. Many studies on flood hazard had been done in prone area in Malaysia, however, the study on flood vulnerability is limited especially on damage assessment. Hence, the aim of this study is to assess the flood damage and to develop a flood depth-damage curve to assist in the assessment of flood risk in Kuantan, Pahang. This study is focusing on residential area in Kuantan. An interview survey was conducted to collect damage data and related information regarding the 2013 Kuantan flood. The average content damage is RM 8,200 while the average structural damage is RM 2,200. The average structural damage for single-storey house is around RM 2,183 while the average content damage is around RM 8,062. The regression analysis shows that the content damage is influenced by type of occupation, and number of storeys while the structural damage is influenced by the type of building material and type of occupation. With R2 of 0.92 for content damage, the flood depth-damage curve obtained for is good enough but the curve for structural damage is poor (R2=0.53) due to the poor quality of data collection. The results obtained from this study can be used to assist in the future flood risk management planning at the study area.